Teaching assistant's handbook - Kay, Janet (London : New York : Continuum, 2006)
The teacher's assistant's role is important and more is being expected of it, yet advice and support can be hard to find. This practical and constructive resource covers each module of the CACHE STA award, and is for students on this course as well as existing assistants and volunteers.
Includes index.
Keywords: Teachers' assistants -- Handbooks, manuals, etc. -- Great Britain